Transformative and restorative consumption behaviors following attachment trauma. Issue 8 (August 2017) - Caldwell, Marylouise; Henry, Paul
Abstract: This study presents a model of how consumers respond to an attachment trauma for which they feel a substantial degree of personal responsibility. The model is derived from an analysis of the lived experiences, stories, and observations of divorced single mothers, who have experienced an attachment trauma as a consequence of a marriage break down. The trauma involves a dramatic loss of normalcy and certainty, accompanied by negative emotions, such as fear and uncertainty, stress and grief, self‐castigation, guilt and shame, and rumination and depression. In an effort to recover from the trauma and return to healthier emotional states, consumers adopt amelioration strategies characterized by self‐compassion, self‐care, and the (re)building of self‐capabilities. Consumption practices—restorative and transformative in nature—facilitate each strategy, as consumers strive to regain the confidence, sense of control, and equilibrium destroyed by the trauma. The model arguably provides a useful lens to understand other kinds of traumatic events where a sense of heightened personal responsibility prevails.